The Feminine Body and the Culture of Care. Issue 3 (3rd July 2022) - Rodriguez, Marta
Abstract : Can we speak of a feminine approach to caring for the body? If there is such an approach, how does culture influence or even construct it? Do we need a new culture of care in the medical field? What can a woman's contribution be to transform culture in this area? In this analysis, I take the human body and its way of being in the world as my starting point, so that we could speak, using Sartrean terminology, of a 'psychical body'. Then I consider the symbiosis that occurs during pregnancy, and I speak of it as a 'relational modality', that gives an 'existential orientation' to women, whether or not they are biological mothers. Finally, I show some implications of this relational modality for the culture of care.